Developing IoT Systems: It's All About the Software. - Kubitza, Thomas; Bader, Patrick; Mogerle, Matthias; Schmidt, Albrecht (Computer (00189162), 2020)
For the Internet of Things to move from the lab to the real world, software and application development must be simplified, and collaboration must increase. We designed an operating system and a development environment that facilitate the process and supports a range of users.